2011
DOI: 10.1615/jwomenminorscieneng.2011002386
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Mathematical and Computer Self-Concept Among Female College Students: Is There a Role of Single-Sex Secondary Education?

Abstract: At a time when women remain significantly underrepresented in many science, technology, engineering, and mathematics (STEM) fields in college and in the workforce, it is important to consider how educational environments contribute to women's beliefs about their STEM-related skills and abilities. This study examines how one strategy-single-sex secondary education-correlates with mathematical and computer self-concept among women entering college. The study uses multilevel modeling to address secondary school-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Researchers must continue to explore how troublesome problems within STEM classrooms and programs, such as stereotypes and lack of self-efficacy based on gender and age (e.g., Espinosa 2011; Richardson and King 1998;Sax et al 2011), may be resolved. In addition, empirical efforts should be further devoted to understanding the nuanced and complex processes of developing interest and grit in pursuing an upward transfer pathway in STEM fields of study among female and older students, along with other underrepresented student groups (Dowd 2012;Gabbard et al 2006;Jackson and Laanan 2011;Palmer and Wood 2013).…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…Researchers must continue to explore how troublesome problems within STEM classrooms and programs, such as stereotypes and lack of self-efficacy based on gender and age (e.g., Espinosa 2011; Richardson and King 1998;Sax et al 2011), may be resolved. In addition, empirical efforts should be further devoted to understanding the nuanced and complex processes of developing interest and grit in pursuing an upward transfer pathway in STEM fields of study among female and older students, along with other underrepresented student groups (Dowd 2012;Gabbard et al 2006;Jackson and Laanan 2011;Palmer and Wood 2013).…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…The major purpose of the current study is to assess the impact of one particular institution that can influence students' STEM outcomes -single-sex schools (Mael, 1998;Sax, Shapiro, & Eagan, 2011;Sullivan, 2009). In this study we first examine causal effects of single-sex schools on high school seniors' national college entrance exam scores on math for seven different senior cohorts (2004 to 2011, except 2007) in South Korea (hereafter, Korea).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, social self-efficacy was found negatively related to the academic achievement and be linked to a sense of loneliness (Carroll, et al, 2009;Wei, & Zakalik, 2005). In addition, a series of self-concept study revealed that the institutional characteristics (both secondary schools and colleges) contributed to the gender differences on students' self-concept (Sax, 1994;Sax, 1996;Sax, Shapiro, & Eagan, 2011).…”
Section: Statement Of the Problemmentioning
confidence: 99%